2016
DOI: 10.1016/j.addbeh.2016.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Childhood cigarette and alcohol use: Negative links with adjustment

Abstract: Children who initiate cigarette or alcohol use early—during childhood or early adolescence—experience a heightened risk of nicotine and alcohol dependence in later life as well as school failure, crime, injury, and mortality. Using prospective intergenerational data from the Millennium Cohort Study (MCS), we investigate the association between early substance use initiation (cigarettes or alcohol) and age 11 school engagement, academic achievement, and wellbeing. The ongoing MCS tracks the development of a nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 41 publications
2
10
0
1
Order By: Relevance
“…This investigation emphasizes that the highest prevalence of tobacco experimentation occurred in boys and these results show the adolescent's behavior towards tobacco use, and that increased, worldwide, from the twentieth century, associated with the idea of masculinity, strength, and power, influenced by advertisements that conveyed the image of success 37 . Concerning gender, the results corroborate several previous studies and point out that being male is a predominant factor for tobacco experimentation 20,27,[38][39][40][41] .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This investigation emphasizes that the highest prevalence of tobacco experimentation occurred in boys and these results show the adolescent's behavior towards tobacco use, and that increased, worldwide, from the twentieth century, associated with the idea of masculinity, strength, and power, influenced by advertisements that conveyed the image of success 37 . Concerning gender, the results corroborate several previous studies and point out that being male is a predominant factor for tobacco experimentation 20,27,[38][39][40][41] .…”
Section: Discussionsupporting
confidence: 90%
“…The same result was observed in Argentina 19 and the United Kingdom 20 . However, in the study Health Behavior in School-Aged Children (HBSC), it was observed that, among adolescents aged 11 and 13 years, no difference was found in weekly consumption between genders, but, at the age of 15 years, alcohol consumption is higher in boys 21 .…”
Section: Discussionsupporting
confidence: 82%
“…Other common related articles (n = 6/21) presented other risks associated with childhood period that are not a disease but may cause the deterioration of children's health and lead to a disease. Other interesting areas covered in literature that are related to these causes are germs and bacteria [197], contaminated drinking water [198], [199], childhood cigarette and alcohol use [22], smoke exposure [200], and risk of hospitalization [201].…”
Section: ) Risksmentioning
confidence: 99%
“…Some researchers encouraged assessment in case language abilities and prosocial behavior [3] and the monitoring of behavioral development for children to investigate maltreatment [194]. Youth adjustments should be studied in relation to early substance use patterns [22]. Health characterization pattern should be investigated in relation to different races [139].…”
Section: ) Other Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation